Trajectories of maternal depression: A 27-year population-based prospective study - Najman, J.; Plotnikova, M.; Williams, G.; Alati, Rosa; Mamun, A.; Scott, J.; Wray, N.; Clavarino, A. (-, 2017)
Copyright © Cambridge University Press 2016. Aims. To identify distinct trajectories of depression experienced by a population-based sample of women over a 27-year period and to assess the validity of the derived trajectories. Method. The Mater University of Queensland Study of Pregnancy is a birth cohort study which commenced in 1981. Women (N = 6753) were interviewed at their first clinic visit, at 6 months, then 5, 14, 21 and 27 years after the birth of their child, using the Delusions Symptoms - States Inventory. Some 3561 (52.7%) women were followed up at 27 years, with 3337 (49.4%) of the sample completing the Composite International Diagnostic Interview (CIDI). Depression trajectories over a 27-year period were identified using Latent Class Growth Modelling (LCGM). LCGM was used to identify respondents with similar patterns of depression over a 27-year period. At the 27-year follow-up women who completed the CIDI, were stratified according to their trajectory group membership. Results. Three trajectory groups, each with different life-course patterns of depression were identified. The low/no symptoms of depression trajectory group comprised 48.4% of women. The mid-depression group (41.7%) had a consistent pattern of occasional symptoms of depression. The high/escalating trajectory group comprised 9.9% of the women in the study. We then examined each trajectory group based on their completion of the CIDI at the 27-year follow-up. Using the CIDI, 27.0% of women in the study had met the DSM-IV criteria for lifetime ever depression by their mean age of 46.5 years. The responses to the CIDI differed greatly for each of the trajectory groups, suggesting that the trajectories validly reflect different life histories of depression. The high/escalating trajectory group had an earlier age of first onset, more frequent episodes, longer duration of each episode of depression and experienced higher levels of impairment for their episodes of depression. For the high symptoms trajectory group, clinically significant depression is estimated to be experienced by women almost one in every 6 days of their life. Conclusion. While symptoms of depression are commonly experienced in a large community-based sample of women, a minority of women experience many episodes of depression in their lifetime. It is this group of women who are most impaired and should be of most concern, and who should be the main target of prevention and treatment initiatives.